KEPUTUSAN PEMBELIAN PRODUK STARBUCKS: Studi Pada Starbucks One Belpark Mall, Jakarta - Mathilda Aquita Haumahu, - (2019)
This research is a quantitative research that aims to determine the effect of product quality, brand image, and price on purchasing decisions. The population in this study was starbucks lovers at one belpark mall. The sample size was taken as many as 75 respondents, with non probability sampling method, especially purposive sampling. Data collection is done through the distribution of questionnaires. The analysis technique used is the method of PLS (Partial Least Square) analysis. The result of this study indicate that (1) product quality has a significant influence on purchasing decisions with path coefficient values of 0,741. (2) brand image has a significant influence on purchasing decisions with path coefficient values of 0,457. (3) prices has not influence on purchasing decisions with a path coefficient of -0,300.